Non-invasive glioblastoma immunoprofiling by printed peptide arrays - Mock, Andreas; Herold-Mende, Christel (OncoImmunology, 2016)
Immune monitoring assays for patient stratification and treatment efficacy in clinical trials are in demand. We have recently described a cost-effective non-invasive assay to determine the immune status of glioblastoma patients. Profiling antitumor serum antibodies by customized printed peptide arrays identified response against a tenascin-C (TNC) peptide as a robust prognostic biomarker.